Feminization in Digital Political Memes: Strategies of Delegitimization and the Reproduction of Patriarchy through Symbolic Violence - Salsa Elsa Ulandari; Naura Allevia Tamsil; Ika Arinia Indriyani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The growth of social media has led to the emergence of a number of new political communication media, such as the use of digital memes to denigrate and criticize political figures and state officials. The purpose of this study is to analyze how feminization in digital political memes perpetuates patriarchal institutions through gender-based symbolic violence and is used as a tactic to delegitimize masculine political actors. This study uses a descriptive qualitative methodology that combines representational analysis and visual discourse analysis. Purposeful sampling was used to select 13 political memes that met the research requirements from memes circulating on TikTok and Instagram between 2020 and 2025. The findings show how feminization practices in digital political memes are created by visually manipulating the bodies of male politicians with feminine characteristics including dresses, hijabs, makeup, mukena (prayer attire), and specific body positions. These depictions act as symbolic tactics to challenge the legitimacy of leadership associated with masculinity, while also being humorous or politically satirical. Furthermore, the widespread use of memes on social media suggests that symbolic violence, which normalizes gender stereotypes and upholds patriarchal power relations in digital political culture, is being reproduced online.